2018
DOI: 10.3390/e20040306
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Non-Equilibrium Driving with Nucleotide Selectivity at Kinetic Checkpoints in Polymerase Fidelity Control

Abstract: High fidelity gene transcription and replication require kinetic discrimination of nucleotide substrate species by RNA and DNA polymerases under chemical non-equilibrium conditions. It is known that sufficiently large free energy driving force is needed for each polymerization or elongation cycle to maintain far-from-equilibrium to achieve low error rates. Considering that each cycle consists of multiple kinetic steps with different transition rates, one expects that the kinetic modulations by polymerases are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…On the other hand, biochemical and kinetic studies have demonstrated that a slow step follows the initial NTP binding to allow for the nucleotide insertion (25). We have also shown generically that the slow or rate-limiting step can play a significant role in the fidelity control of the template-based polymerization (26). It is highly likely that the non-proofreading T7 RNAP relies on the slow nucleotide insertion to conduct substantial nucleotide selection, or transcription fidelity control.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, biochemical and kinetic studies have demonstrated that a slow step follows the initial NTP binding to allow for the nucleotide insertion (25). We have also shown generically that the slow or rate-limiting step can play a significant role in the fidelity control of the template-based polymerization (26). It is highly likely that the non-proofreading T7 RNAP relies on the slow nucleotide insertion to conduct substantial nucleotide selection, or transcription fidelity control.…”
Section: Introductionmentioning
confidence: 97%
“…Following the previous clues (22), both an on-path and an off-path insertion processes of the non-cognate nucleotides were probed for the free energy calculations. Finally, we were able to infer the selection free energetics down to the catalytic stage by fitting with experimentally measured error rates via a chemical master equation (CME) approach onto the T7 RNAP elongation kinetics (26,31). This way, we completely characterized the fidelity control in this prototypical viral transcription system, with both classical structural dynamics and free energetic details.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently studied transcription elongation of T7 RNAP by combining physical modeling and all-atom MD simulations, addressing both mechano-chemical coupling and fidelity control mechanisms during elongation [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. The mechanochemistry concerns about how the protein machine utilizes chemical free energy to generate mechanical or directional motions, referring to how the chemical synthesis of RNA couples with the polymerase translocation along DNA in the RNAP system.…”
Section: T7 Rna Polymerase As a Minimal Transcription Machine Model Smentioning
confidence: 99%
“…The nucleotide insertion accompanied by a conformational transition from a ‘semi-open’ to the closed form has been suggested to be a slow step during the NAC in T7 RNAP from previous biochemical studies [ 22 ]. It is highly likely that the slow insertion step is employed by the enzyme to substantially scrutinize against non-cognate nucleotide species to achieve sufficiently high transcription fidelity [ 35 ]. In viral T7 RNAP elongation, an elongation error rate reaches to ~10 −4 to 10 −6 for the base mismatch incorporation (e.g.…”
Section: Selective Ratcheting Proceeds Through Slow Nucleotide Insertmentioning
confidence: 99%
See 1 more Smart Citation